1987
DOI: 10.1063/1.98565
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of 13-Å-diam Au clusters using scanning tunneling microscopy

Abstract: Controlled size clusters of Au with a diameter of 13 Å, prepared using a multiple expansion cluster source, have been supported on highly oriented pyrolytic graphite and observed with a scanning tunneling microscope. A reliable constant-current signature for a metallic cluster supported on a graphite substrate is identified. Images of the supported Au clusters are found to exhibit a narrow size distribution and a diameter which is in close agreement with the diameter predicted from conditions in the multiple e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Such clusters have never been studied under UHV using STM. However, 3D clusters nucleated in the gas phase before deposition have been imaged in air [9], but no features of atomic size were observed neither on the clusters nor on the substrate. In this paper we present STM studies of 3D gold clusters grown under UHV at high temperature on clean graphite.…”
mentioning
confidence: 99%
“…Such clusters have never been studied under UHV using STM. However, 3D clusters nucleated in the gas phase before deposition have been imaged in air [9], but no features of atomic size were observed neither on the clusters nor on the substrate. In this paper we present STM studies of 3D gold clusters grown under UHV at high temperature on clean graphite.…”
mentioning
confidence: 99%
“…However, from the overall size of the image it m a y be concluded that the short edges (ca. i.e., their size is similar to that of Ag or Au clusters on H O P G , prepared by plating or evaporation (3,(10)(11)(12). On the other hand, we were able to observe m u c h smaller clusters that looked very m u c h like groups of Pd-triplets (14).…”
Section: Resultsmentioning
confidence: 74%
“…By evaporation (10)(11)(12) or plating (3) techniques, clusters of metals (e.g., Ag or Au) can also be prepared on original HOPG. However, these clusters seem to be fairly mobile on the HOPG surface (10).…”
Section: Resultsmentioning
confidence: 99%